"The Effects of Temperature and PH on Settlability of Activated Sludge Flocs" - Gh Ghanizadeh; R Sarrafpour (Tehran University of Medical Sciences, 2001)
The effluent quality of a sewage treatment plant using activated sludge process and finally secondary treatment depends on the flocculation efficiency and settling of the flocs. The survey of various treatment processes in water and wastewater treatment shows that temperature and pH are the important factors affecting efficiency of flocculation and settling properties. This study was performed to determine the effects of pH and temperature on settling of the flocs in activated sludge process. It was carried out for three months in two phases, using mixed liquor suspended solids (MLSS), obtained from aeration tank from one of wastewater treatment plants in Tehran. In the primary phase, the temperature of samples was increased from 15°C to 35°C. As a result, the sludge volume index (SVI) and effluent suspended solids increased and consequently, COD removal percent decreased. In the second phase, the pH was increased from 5.7 to 9. As a result, SVI and effluent suspended solids decreased and COD removal percent increased.